Industrial Obelisks: Working-class memory and Barcelona's chimney-monuments - Rosa, Brian (Journal of historical geography, 2024)
This study critically examines the transformation of industrial chimneys into monuments within Barcelona's deindustrializing urban landscapes. Since the 1970s, redevelopment contexts and reimaging strategies have led to the conservation of industrial chimneys as public art and historic monuments. This paper explores the intersection of urban memory, heritage, and transformation in Barcelona, highlighting the absence of a coherent ‘Authorized Heritage Discourse’ and the resulting ambiguity in the meaning of these monuments. Analyzing this unique heritage practice, the study considers its impact on historic memory and working-class identity within the city's urban fabric. The research situates chimney-monuments within broader discussions on postindustrial redevelopment, urban design, heritage conservation, and public memory amidst deindustrialization. By examining the symbolic and material dimensions of industrial chimneys within Barcelona's political-economic shifts and contemporary social movements, the paper unpacks their polysemic meanings. This analysis contributes to local debates and reflects broader European trends. The study questions how these monuments are integrated into working-class memory politics and shifting heritage regimes. Recognizing that historic monuments are dynamic material and cultural processes subject to ongoing resignification, the paper concludes with a discussion on the potential roles of insurgent heritage practices in connecting past and present social struggles. •Examines how Barcelona's industrial chimneys have been repurposed amidst deindustrialization and urban redevelopment.•Analyzes how these chimney-monuments influence historic memory and working-class identity in the city.•Discusses the lack of a coherent heritage discourse and the resulting debates among historians, activists, and urban designers.•Investigates public perceptions through surveys and an exhibition, emphasizing industrial pasts and working-class landscapes.•Highlights the evolution of Barcelona's heritage policies and the role of urban design in preserving landmarks, influenced by working-class memory activism.